PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA PELAJARAN IPA SISWA KELAS VII SMP - Berlianti, Nindha Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2017)
The Beginning of observation conducted in SMP PGRI Ngraho Bojonegoro Class VIIA. The observation show that student Critical Thinking skills is lack in Acquaintance stuff And solve problem, make hypothesis, make conclusions and develop opinion, with average fg ability Critical Thinking at 53, 2%. Based on that fact learning model need to be apply. The learning model can build ability of critical thinking like problem-Based Learning. The purpose of this observation for knowing the impact of learning model with basic problem to develop student crtical thinking skill. The research conducted by Penelitian Tindakan Kelas (PTK), which consists of two cycles in eight times meeting. The subject of the observation is VII-A SMP PGRI Ngraho Bojonegoro student with total of 30 students. The main topic that used by this observation is statistic and scale. The instrument of this observation are RPP, LKS, problem based learning attending observation sheet, critical thinking skills observation sheet and field notes. The technique of data analysis are data reduction, data presentation and draw conclusion. The result of the observation shows that problem-Based Learning can develop student critical thinking skills. That result show with developing of average percentage of critical thinking skills from 53,2% in beginning of observation rise to 58,5% in cycle I and 73,3% in cycle II. Keywords: Problem-Based Learning, Critical Thinking Skills, Learning Science